2019
DOI: 10.1101/2019.12.13.871558
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered cortical gyrification in adults who were born very preterm and its associations with cognition and mental health

Abstract: Background The last trimester of pregnancy is a critical period for the establishment of cortical gyrification and altered folding patterns have been reported following very preterm birth (< 33 weeks of gestation) in childhood and adolescence. However, research is scant on the persistence of such alterations in adulthood and their associations with cognitive and psychiatric outcomes.Methods We studied 79 very-preterm adults and 81 age-matched full-term controls. T1-weighted images were used to measure local gy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 76 publications
(38 reference statements)
4
14
0
Order By: Relevance
“…Our results converge with previous research demonstrating differences in local folding patterns in cingulate and temporal regions 9 , 10 , 37 , 52 and empirically integrates these spatially localized differences in support of hypotheses of aberrant fronto-temporal and salience network connectivity underpinning the experience of hallucinations in schizophrenia 15 17 , 53 . We advance prior research on sulcal asymmetries in the general population and in developmental and psychiatric disorders 21 , 25 28 , 30 , 36 , showing a reduction of the typical leftward PCS asymmetry in schizophrenia patients with hallucinations, due to a shorter left hemisphere PCS, compared to patients without hallucinations and to healthy controls. The rightward STS asymmetry was also lower, with a significantly diminished mean depth of the right STS in H+ patients compared to HCs.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Our results converge with previous research demonstrating differences in local folding patterns in cingulate and temporal regions 9 , 10 , 37 , 52 and empirically integrates these spatially localized differences in support of hypotheses of aberrant fronto-temporal and salience network connectivity underpinning the experience of hallucinations in schizophrenia 15 17 , 53 . We advance prior research on sulcal asymmetries in the general population and in developmental and psychiatric disorders 21 , 25 28 , 30 , 36 , showing a reduction of the typical leftward PCS asymmetry in schizophrenia patients with hallucinations, due to a shorter left hemisphere PCS, compared to patients without hallucinations and to healthy controls. The rightward STS asymmetry was also lower, with a significantly diminished mean depth of the right STS in H+ patients compared to HCs.…”
Section: Discussionsupporting
confidence: 55%
“…We hypothesize that auditory hallucinations in schizophrenia patients, and the accompanying patterns of brain function, result from alterations to the maturational trajectories in temporal and cingulate regions, and thus their structural covariance. Mechanistic predictions follow, including the role of genes involved in driving the maturational trajectories of cortical patterning 64 and the impact of events that disrupt fetal neurodevelopment 20 , 21 , 62 , 63 . Longitudinal studies following prenatal cohorts until adult life will be required to establish such predictions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered LGI has been reported in children (Kesler et al, 2006; Zhang et al, 2015), adolescents (Ganella et al, 2015) as well as adults (Papini et al, 2020) who were born very preterm and the functional consequences of altered LGI has been demonstrated by Papini et al (2020) who reported association between higher LGI and higher IQ and lower psychopathology scores in both very preterm and control adults. LGI is also altered in psychiatric disorders with a prominent neurodevelopmental component.…”
Section: Introductionmentioning
confidence: 96%
“…Preterm birth, known to be linked to aberrant in utero cortical development, is associated with defects in cortical folding that appear to persist in adult life [ 4 ]. Aberrant cortical folding in adults related to preterm birth relates to negative cognitive and mental health outcomes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%